Lactobacillus rhamnosus CRL1505 enhances systemic and respiratory innate immune response in immunocompromised malnourished mice - Herrera, Héctor Matías (2013)
The effect of Lactobacillus rhamnosus CRL1505 on blood and bone marrow (BM) myeloid cells and their correlation with resistance against Streptococcus pneumoniae infection was evaluated in protein-malnourished mice. Repletion of malnourished mice with supplemental L. rhamnosus improved recovery of BM responsiveness against the infectious challenge through increase in myeloid progenitors and mobilisation of granulocytes. The CRL1505 strain normalised the number of Gr1+ cells and Gr1low/Gr1high cells balance in BM. These changes in BM correlated with improved neutrophils recruitment, higher phagocytic activity and increased resistance against pneumococcal infection in probiotic-treated mice. This research provides strong evidence of the importance of dietary supplementation with probiotic bacteria to reverse alterations in myeloid progenitors in malnourished mice. The present results strongly suggest that the CRL1505 strain could be used in the development of probiotic foods, which would be especially useful for the recovery of immunocompromised hosts.